AEROBIC EXERCISE DECREASE BODY WEIGHT GAIN OF PRIMIGRAVIDA WITH HYPERTENSION HISTORY - S. Hutagaol, Hotma (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: To determine the effect of aerobic exercise on body weight gain in primigravida mothers with a history of hypertension Method: This study used a quasi experimental with pre and post control group design of twenty primigravida mothers who were divided into 2 groups: those who did aerobic exercise for 12 weeks (intervention group) and did not do aerobic exercise (control group), and then body weight gain were taken in both groups. Result: The research results are body weight gain during the 12 weeks intervention was lower in the intervention group (Mean= 0.44) compared to the control group (Mean= 0.58) and was statistically significant (p= 0.03). Conclusion: The conclusion of this study that aerobic exercise can be the alternative way for pregnant women mostly to primigravida with a history of hypertension to decrease their body weight gain during pregnancy.